Classical Literature And The Conception Of The Monster-Mother (Journal of Namibian Studies : History Politics Culture, 2023)
Second-wave feminism inspired classical scholars to willfully disengage from the conservative disciplinary focus on father-son narratives and to instead delve into the ancient literary, documentary and material remains of the lives of women in antiquity- wives and sisters, mothers and daughters. Matrifocal studies of classical antiquity then, is a relatively recent literary development. One such study-area is of monster mothers, who actually show up pretty early in ancient tales- Medea, who murders her own children to punish her faithless husband, Clytemnestra who stabs her husband Agamemnon in his bath for sacrificing their daughter on the altar to propitiate the gods and gain favourable winds for the Greek ships heading for Troy, Grendel’s demonic mother who kills a Danish warrior to avenge Grendel’s death at Beowulf’s hands. This paper will explore the narratives of monster-mothers and the damage they inflict, which often tends to be more psychic than physical.